Determinants of MSME Sustainability: A Regression-Based Study in Labuhanbatu - Ritonga, Mulkan; Nasution, Ade Parlaungan; Muti’ah, Rahma (Advance Sustainable Science Engineering and Technology, 2025)
This study aims to identify factors that influence the development of healthy and independent MSMEs in Labuhanbatu Regency, Indonesia.  The research method uses a quantitative approach with primary data collection through interviews and questionnaires distributed to 342 MSME actors in Labuhanbatu Regency. The sample was taken using a stratified random sampling technique based on the 2019 MSME population. The data were analyzed using multiple regression techniques to test the effect of the independent variables partially and simultaneously on the dependent variable. The results showed that education and skills (β = 25.299, p < 0.01), locus of control (β = 4.452, p < 0.01), government support and policies (β = 18.001, p < 0.01), and access to capital and financial resources (β = 9.332, p < 0.01) have a positive and significant influence on the development of healthy and independent MSMEs. In contrast, financial literacy (β = 1.025, p > 0.1), partnership networks (β = 1.005, p > 0.1), and infrastructure and technology (β = 1.087, p > 0.1) did not contribute significantly in this study. These findings emphasize the need for human resource capacity building and government policies that support access to capital as key strategies to encourage the sustainability and self-reliance of MSMEs in the region.